2005
DOI: 10.2169/internalmedicine.44.696
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-ankle Pulse Wave Velocity in Japanese University Students

Abstract: Objective Pulse wave velocity (PWV) correlates well with arterial distensibility and stiffness and is a useful non-invasive index to assess arteriosclerosis. The present study was conducted to evaluate the validity of noninvasive brachial-ankle PWV (baPWV) measurements in overweight young adults.Methods Three hundred and fifty-three students were voluntarily enrolled (mean age: 20±2, 93 women and 260 men). The subjects were divided into three groups: normal (18.5< = body mass index (BMI) <25 n=120), overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
(25 reference statements)
2
21
1
2
Order By: Relevance
“…19,40 baPWV 16,17 was also useful to predict the early stages of atherosclerosis. 18,19 In contrast, Nishi et al 41 also observed a significant but poor correlation between baPWV and intima-media thickness in subjects with diabetes and no significant relationship with baPWV in the presence of plaques. Further investigation is needed to assess usefulness of baPWV for detection of early atherosclerosis.…”
Section: Macroscopic and Microscopic Findings Of The Aortamentioning
confidence: 96%
See 3 more Smart Citations
“…19,40 baPWV 16,17 was also useful to predict the early stages of atherosclerosis. 18,19 In contrast, Nishi et al 41 also observed a significant but poor correlation between baPWV and intima-media thickness in subjects with diabetes and no significant relationship with baPWV in the presence of plaques. Further investigation is needed to assess usefulness of baPWV for detection of early atherosclerosis.…”
Section: Macroscopic and Microscopic Findings Of The Aortamentioning
confidence: 96%
“…There are pathological studies indicating that atherosclerotic lesions begin even in childhood. 37,38 Several investigators have demonstrated that baPWV showed a significant correlation with MAP in young adults 18,36 and with SBP and DBP in children. 35,39 In the Bogalusa Heart Study, Li et al 34 reported that childhood blood pressure was a predictor of arterial stiffness in adulthood.…”
Section: Macroscopic and Microscopic Findings Of The Aortamentioning
confidence: 99%
See 2 more Smart Citations
“…Glycemic control and hyperinsulinemic state are important factors that determine the PWV in diabetic patients. The baPWV was significantly higher in obese [body mass index (BMI) >30 kg/m 2 ] male subjects than in the overweight (25< BMI <30 kg/m 2 ) subjects of Japan university students, and in the male with nonalcoholic fatty liver disease (NAFLD) than in those without NAFLD (10).…”
mentioning
confidence: 99%